ISSUES OF QUALITY AND ACCESS TO EDUCATION IN TIMOR-LESTE IN THE POST-INDEPENDENCE ERA - António José Correia; Fernando Luís da Costa Araujo; Alexandre Ribeiro de Jesus; João Manuel da Silva (International Journal of Education and Social Science Studies, 2025)
This study aims to identify the key factors influencing disparities in access to basic and secondary education and to examine their implications for learning quality in Timor-Leste. Using a qualitative descriptive method based on literature review and document analysis, the research reveals that the education system in Timor-Leste faces deeply interconnected structural barriers. Geographical isolation, widespread poverty, poor school infrastructure, and a lack of learning resources are the primary obstacles to educational access, especially in rural and remote areas. On the other hand, the quality of education is undermined by low teacher qualifications, limited pedagogical training, and a national curriculum that is insufficiently contextualized to local needs. The use of Portuguese and Tetun as the official languages of instruction further exacerbates learning gaps, particularly for students from communities that speak local languages. These factors contribute to high dropout rates, poor literacy and numeracy outcomes, and a high rate of grade repetition. Although some progress has been made through school construction, teacher training, and curriculum reform, the impact remains uneven across different regions. Therefore, a holistic and sustained approach is urgently needed, involving inclusive policies, investment in human resources, and strengthened collaboration between the government, international donors, and local communities. Improving the education system is essential not only for individual empowerment but also for Timor-Leste’s long-term social, economic, and peacebuilding goals.